Thermal Conductive Sheet
The thermal conductive sheet, made with a resin and particulate filler, addresses the challenge of achieving smooth surfaces and uniform thickness while maintaining high thermal conductivity in the thickness direction, through a precise slicing method using a blade with specific surface roughness and geometry.
Patent Information
- Application Number
- JP2023172212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2039-02-26
AI Technical Summary
Existing methods struggle to produce thermal conductive sheets with both main surfaces smooth and uniform thickness, while maintaining sufficient thermal conductivity in the thickness direction.
A thermal conductive sheet comprising a resin and particulate filler, with a thermal conductivity of 15 W/m·K or more in the thickness direction, a standard deviation of thickness of 3.5 μm or less, and surface roughness Sa of both main surfaces of 3.00 μm or less, achieved through a manufacturing method involving slicing with a blade having specific surface roughness and geometry.
The resulting thermal conductive sheet achieves smooth surfaces, precise thickness control, and enhanced thermal conductivity in the thickness direction, ensuring effective heat transfer and improved contact with heat radiators.
Smart Images

Figure 0007658402000002 
Figure 0007658402000003 
Figure 0007658402000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive sheet and a method for manufacturing the thermally conductive sheet. [Background technology]
[0002] In recent years, the amount of heat generated by electronic components such as plasma display panels (PDPs) and integrated circuit (IC) chips has increased as their performance has improved. As a result, it has become necessary to take measures to prevent malfunctions caused by temperature rises in electronic devices that use these components.
[0003] As a countermeasure against functional failures due to temperature rise of electronic components, a method of promoting heat dissipation by attaching a heat sink, a heat sink plate, a heat sink fin, or other heat sink made of metal to a heat source such as an electronic component is generally adopted. When using a heat sink, a sheet-like member having thermal conductivity (thermal conductive sheet) is used to efficiently transfer heat from the heat source to the heat sink. For example, a thermal conductive sheet containing a resin and a particulate filler is sandwiched between the heat source and the heat sink, and the heat source and the heat sink are brought into close contact with each other via the thermal conductive sheet, thereby transferring heat from the heat source to the heat sink. Conventionally, attempts have been made to improve the properties of thermal conductive sheets (see, for example, Patent Documents 1 and 2).
[0004] Patent Document 1 discloses a method for obtaining a thermally conductive sheet by slicing a resin molded body with only one blade, in which a resin molded body is slidably supported by a slide surface and a blade with a tip protruding from the slide surface is supported from the opposite side of the resin molded body across the slide surface, while the resin molded body is pressed against the slide surface and slid, and the resin molded body is obtained by slicing the resin molded body with only the one blade. According to Patent Document 1, the thickness accuracy of the thermally conductive sheet obtained by the above-mentioned method can be improved.
[0005] Patent Document 2 discloses a method for obtaining a thermally conductive sheet by slicing a laminate obtained by stacking primary sheets containing a resin and a particulate carbon material in the thickness direction at an angle of 45° or less with respect to the stacking direction, and then pressurizing the sheet obtained by slicing. According to Patent Document 2, the thermally conductive sheet obtained by the above-mentioned method can exhibit excellent thermal conductivity even when used at a relatively low clamping pressure. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5621306 specification [Patent Document 2] JP 2018-67695 A Summary of the Invention [Problem to be solved by the invention]
[0007] Here, in recent years, in order to ensure good adhesion between the heating element and the heat sink via the thermally conductive sheet while uniformly transferring heat from the heating element to the heat sink, there has been a demand to make both main surfaces of the thermally conductive sheet smooth and to improve the thickness accuracy of the thermally conductive sheet. However, with the above-mentioned conventional methods, it was difficult to produce a thermally conductive sheet having both smooth main surfaces and a uniform thickness while ensuring that the thermally conductive sheet exhibits excellent thermal conductivity in the thickness direction.
[0008] Therefore, an object of the present invention is to provide a thermally conductive sheet having both smooth main surfaces, sufficient thickness accuracy, and capable of transferring heat well in the thickness direction, and a method for manufacturing such a thermally conductive sheet. [Means for solving the problem]
[0009] The present inventors have conducted intensive research to achieve the above object. First, the present inventors attempted to improve the thickness accuracy of the thermally conductive sheet by applying pressure when slicing using a planer as described in Patent Document 1. However, according to the research of the present inventors, it has become clear that when the sheet is pressed when slicing using a planer, it is difficult to ensure sufficient smoothness of both main surfaces. Based on this, the present inventors have found that in a thermally conductive sheet containing a resin and a particulate filler, if the standard deviation of the thickness is set to a predetermined value or less, the thermal conductivity in the thickness direction is set to a predetermined value or more, and the surface roughness Sa of both main surfaces is set to a predetermined value or less, a thermally conductive sheet can be obtained in which both main surfaces are smooth, have sufficient thickness accuracy, and can transfer heat well in the thickness direction, and thus the present invention has been completed.
[0010] That is, the present invention aims to advantageously solve the above problems, and the thermally conductive sheet of the present invention is characterized in that it contains a resin and a particulate filler, has a thermal conductivity in the thickness direction of 15 W / m·K or more, a standard deviation of the thickness of 3.5 μm or less, and both main surfaces have surface roughnesses Sa of 3.00 μm or less. In this way, a thermally conductive sheet that contains a resin and a particulate filler, and has a thermal conductivity in the thickness direction of the above value or more, a standard deviation of the thickness of the above value or less, and both main surfaces have surface roughnesses Sa of the above value or less, has both main surfaces that are smooth, has sufficient thickness precision, and can transfer heat well in the thickness direction. In the present invention, the "thermal conductivity in the thickness direction" can be calculated using the method described in the Examples of this specification. In addition, in the present invention, the "standard deviation of thickness" is a value obtained by measuring the thickness at any five points on the thermal conductive sheet and from these measured values, and can be calculated, for example, using the method described in the examples of this specification. Furthermore, in the present invention, the "surface roughness Sa of both main surfaces" is a value obtained in accordance with the international standard ISO 25178, and can be calculated using the method described in the examples of this specification. In the present invention, "both main surfaces" refers to the surface of the thermally conductive sheet having the largest area and the surface opposite to that surface.
[0011] Here, the thermally conductive sheet of the present invention preferably has an average thickness of 250 μm or less. When the average thickness of the thermally conductive sheet is equal to or less than the above value, heat can be more effectively transferred in the thickness direction of the thermally conductive sheet. In the present invention, the "average thickness" is a value obtained by measuring the thickness at any five points on the thermal conductive sheet and from these measured values, and can be calculated, for example, using the method described in the examples of this specification.
[0012] In addition, the heat conductive sheet of the present invention preferably contains the particulate filler in an amount of 30% by volume or more and 55% by volume or less. If the volume ratio of the particulate filler in the heat conductive sheet is within the above range, the thermal conductivity of the heat conductive sheet in the thickness direction is increased, and the heat can be transferred more effectively in the thickness direction of the heat conductive sheet, and the thickness precision can be further improved while maintaining the flexibility of the heat conductive sheet.
[0013] In the thermal conductive sheet of the present invention, the particulate filler preferably has a volume average particle diameter of 30 μm to 150 μm. If the volume average particle diameter of the particulate filler is within the above range, the thermal conductive sheet can be more effectively heat-transferred in the thickness direction, and the main surface smoothness and thickness accuracy of the thermal conductive sheet can be further improved. In the present invention, the "volume average particle size" can be measured in accordance with JIS Z8825, and refers to the particle size at which the cumulative volume calculated from the small diameter side is 50% in the particle size distribution (volume basis) measured by a laser diffraction method.
[0014] Furthermore, the thermally conductive sheet of the present invention preferably has an absolute difference between the surface roughness Sa of one main surface and the surface roughness Sa of the other main surface of 0.40 μm or less. If the absolute difference between the surface roughness Sa of one main surface of the thermally conductive sheet and the surface roughness Sa of the other main surface of the thermally conductive sheet is equal to or less than the above value, the handling properties, such as the ease of gripping with a robot arm, can be improved.
[0015] The present invention also aims to advantageously solve the above-mentioned problems, and a method for manufacturing a thermally conductive sheet of the present invention includes a step of slidably supporting a block body containing a resin and a particulate filler on a sliding surface, and supporting a blade with a tip protruding from the sliding surface, and sliding the block body against the sliding surface while pressing the block body, thereby slicing the block body with the blade, wherein the blade has a first front surface in contact with the block body, a back surface intersecting the first front surface, a blade tip formed at an intersection corner between the first front surface and the back surface, and a second front surface extending from an edge of the first front surface opposite to the blade tip side and positioned closer to the back surface than the first front surface, wherein the length of the first front surface is 0.8 mm or more, and the surface roughness Sa of the first front surface is 1.00 μm or less. In this way, by slicing a block containing resin and particulate filler in a specified manner using a blade whose first front surface has a length and surface roughness Sa within the above-mentioned ranges, it is possible to obtain a thermally conductive sheet which has both smooth main surfaces, sufficient thickness accuracy, and is capable of transferring heat well in the thickness direction. In the present invention, the "surface roughness Sa of the first front surface" can be measured using the method described in the examples of this specification. In this specification, when slicing the block body, the "surface on the side where the cutting portion that contacts the block body is provided" is referred to as the "front surface," and the surface on the side where the thermally conductive sheet is discharged from the block body (the surface opposite to the front surface on which the cutting portion that initially contacts the block body is provided) is referred to as the "back surface."
[0016] In the method for producing a thermally conductive sheet of the present invention, the second front surface preferably has a surface roughness Sa of 1.00 μm or less. If the surface roughness Sa of the second front surface is equal to or less than the above value, the surface smoothness of the thermally conductive sheet obtained by slicing the block body can be more reliably ensured. In the present invention, the "surface roughness Sa of the second front surface" can be calculated, for example, by using the method described in the examples of this specification.
[0017] The method for manufacturing a thermal conductive sheet of the present invention can further include a step of stacking a plurality of primary sheets containing a resin and a particulate filler in the thickness direction, or folding or rolling the primary sheets, prior to the slicing step, to obtain the block body. In this specification, the terms "stacking", "folding" and "winding" may be collectively abbreviated as "stacking, etc." Effect of the Invention
[0018] According to the present invention, it is possible to provide a thermally conductive sheet having both smooth main surfaces, sufficient thickness accuracy, and capable of excellent heat transfer in the thickness direction, as well as a method for manufacturing the thermally conductive sheet. [Brief description of the drawings]
[0019] [Figure 1] 1A to 1C are explanatory diagrams showing a process for producing a thermally conductive sheet using an example of a method for producing a thermally conductive sheet according to the present invention. [Diagram 2] FIG. 13 is a plan view showing how a block body (laminated body) is sliced at a slide angle β. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail. The thermally conductive sheet of the present invention can be used, for example, by being sandwiched between a heat generating body and a heat dissipating body when attaching the heat dissipating body to the heat generating body. That is, the thermally conductive sheet of the present invention can be used together with a heat dissipating body such as a heat sink, a heat dissipating plate, or a heat dissipating fin to form a heat dissipating device. The thermally conductive sheet of the present invention can be produced, for example, according to the method for producing a thermally conductive sheet of the present invention.
[0021] (Thermal Conduction Sheet) The thermally conductive sheet of the present invention includes a resin and a particulate filler, and may further include an optional additive. The thermally conductive sheet of the present invention has a thermal conductivity in the thickness direction of 15 W / m·K or more, a standard deviation of the thickness of 3.5 μm or less, and both main surfaces have a surface roughness Sa of 3.00 μm or less. The thermally conductive sheet of the present invention has a thermal conductivity in the thickness direction of 15 W / m·K or more, a standard deviation of the thickness of 3.5 μm or less, and both main surfaces have a surface roughness Sa of 3.00 μm or less, so that both main surfaces are smooth and can transfer heat well in the thickness direction while having sufficient thickness accuracy.
[0022] <Resin> The resin contained in the thermal conductive sheet is not particularly limited, and any resin can be used. For example, the resin can be either a liquid resin or a solid resin. The resin may be used alone or in combination of two or more types. For example, the thermal conductive sheet can contain at least one of a liquid resin and a solid resin, but from the viewpoint of further improving the thickness accuracy of the thermal conductive sheet and more favorably transferring heat in the thickness direction, it is preferable that the thermal conductive sheet contains both a liquid resin and a solid resin.
[0023] <<Liquid resin>> The liquid resin is not particularly limited as long as it is liquid at room temperature and normal pressure, and for example, a thermoplastic resin that is liquid at room temperature and normal pressure can be used. In the present invention, "normal temperature" refers to 23° C., and "normal pressure" refers to 1 atm (absolute pressure).
[0024] Examples of liquid resins include fluororesins, silicone resins, acrylic resins, and epoxy resins. These may be used alone or in combination of two or more. Among them, silicone resins and fluororesins are preferred as liquid resins, and fluororesins are more preferred. If at least one of silicone resins and fluororesins is used as the liquid resin, the flame retardancy of the thermal conductive sheet can be improved. In addition, if a fluororesin is used as the liquid resin, the heat resistance, oil resistance, and chemical resistance of the resulting thermal conductive sheet can be improved.
[0025] <<Solid resin>> The solid resin is not particularly limited as long as it is not liquid at room temperature and normal pressure. For example, a thermoplastic resin that is solid at room temperature and normal pressure, or a thermosetting resin that is solid at room temperature and normal pressure can be used.
[0026] [Thermoplastic resin that is solid at room temperature and pressure] Examples of thermoplastic resins that are solid at room temperature and pressure include acrylic resins such as poly(2-ethylhexyl acrylate), copolymers of acrylic acid and 2-ethylhexyl acrylate, polymethacrylic acid or its esters, and polyacrylic acid or its esters; silicone resins; fluororesins; polyethylene; polypropylene; ethylene-propylene copolymers; polymethylpentene; polyvinyl chloride; polyvinylidene chloride; polyvinyl acetate; ethylene-vinyl acetate copolymers; polyvinyl alcohol; polyacetal; polyethylene terephthalate; polybutylene terephthalate; polyethylene naphthalate; polystyrene; polyacrylonitrile. ; styrene-acrylonitrile copolymer; acrylonitrile-butadiene copolymer (nitrile rubber); acrylonitrile-butadiene-styrene copolymer (ABS resin); styrene-butadiene block copolymer or hydrogenated product thereof; styrene-isoprene block copolymer or hydrogenated product thereof; polyphenylene ether; modified polyphenylene ether; aliphatic polyamides; aromatic polyamides; polyamideimide; polycarbonate; polyphenylene sulfide; polysulfone; polyethersulfone; polyethernitrile; polyetherketone; polyketone; polyurethane; liquid crystal polymer; ionomer; etc. These may be used alone or in combination of two or more. In the present invention, rubber is included in the "resin".
[0027] [Thermosetting resin that is solid at room temperature and pressure] Examples of thermosetting resins that are solid at room temperature and normal pressure include natural rubber, butadiene rubber, isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene propylene rubber, chlorinated polyethylene, chlorosulfonated polyethylene, butyl rubber, halogenated butyl rubber, polyisobutylene rubber, epoxy resin, polyimide resin, bismaleimide resin, benzocyclobutene resin, phenolic resin, unsaturated polyester, diallyl phthalate resin, polyimide silicone resin, polyurethane, thermosetting polyphenylene ether, thermosetting modified polyphenylene ether, etc. These may be used alone or in combination of two or more.
[0028] <<Resin content>> The resin content in the thermal conductive sheet is not particularly limited, but is preferably 35% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, and preferably 95% by mass or less, more preferably 85% by mass or less, and even more preferably 75% by mass or less. If the resin content is 35% by mass or more, the thickness precision of the thermal conductive sheet can be further improved while ensuring the flexibility of the thermal conductive sheet. On the other hand, if the resin content is 95% by mass or less, heat can be transferred more effectively in the thickness direction of the thermal conductive sheet.
[0029] <<Liquid resin content>> In addition, the content of the liquid resin in the resin (in other words, the proportion of the liquid resin in the total of the solid resin and the liquid resin) is not particularly limited, but is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, particularly preferably 60% by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less. If the content of the liquid resin in the resin is 30% by mass or more, the thickness precision can be further improved while ensuring the flexibility of the thermal conductive sheet. On the other hand, if the content of the liquid resin in the resin is 95% by mass or less, the strength suitable for the primary sheet is imparted, making it easier to slice the laminate, and the thickness precision of the obtained thermal conductive sheet can be further improved.
[0030] <Particulate filler> The particulate filler contained in the thermal conductive sheet is not particularly limited as long as it can impart thermal conductivity to the thermal conductive sheet. As such particulate filler, a particulate carbon material having high thermal conductivity can be suitably used. The particulate filler may be used alone or in combination of two or more kinds.
[0031] <<Carbon particles>> The particulate carbon material is not particularly limited, and examples thereof include graphite such as artificial graphite, scaly graphite, exfoliated graphite, natural graphite, acid-treated graphite, expandable graphite, and expanded graphite; carbon black; etc. These may be used alone or in combination of two or more kinds.
[0032] Among the above, it is preferable to use expanded graphite as the particulate carbon material. By using expanded graphite, the thermal conductivity in the thickness direction of the thermal conductive sheet is increased, and heat can be transferred more effectively in the thickness direction of the thermal conductive sheet. Here, the expanded graphite can be obtained by, for example, chemically treating graphite such as flake graphite with sulfuric acid or the like to obtain expandable graphite, and then heat treating the expandable graphite to expand it and then pulverizing it. Examples of the expanded graphite include EC1500, EC1000, EC500, EC300, EC100, and EC50 (all trade names) manufactured by Ito Graphite Industries Co., Ltd.
[0033] <<Properties of particulate filler>> The particulate filler preferably has a volume average particle diameter of 30 μm or more, more preferably 40 μm or more, preferably 150 μm or less, more preferably 100 μm or less, even more preferably 80 μm or less, and particularly preferably 60 μm or less. If the volume average particle diameter of the particulate filler is 30 μm or more, it is presumed that the heat transfer path of the particulate filler in the heat conductive sheet can be well formed, and the thermal conductivity in the thickness direction of the heat conductive sheet is increased. As a result, the heat can be transferred more well in the thickness direction of the heat conductive sheet. On the other hand, if the volume average particle diameter of the particulate filler is 150 μm or less, the main surface smoothness and thickness accuracy of the heat conductive sheet can be further improved.
[0034] The particulate filler preferably has an aspect ratio (major axis / minor axis) of more than 1 and not more than 10, more preferably more than 1 and not more than 5. If the particulate filler has an aspect ratio of more than 1 and not more than 10, it is presumed that the particulate filler is easily well oriented in the thickness direction in the thermal conductive sheet, and the thermal conductivity of the thermal conductive sheet in the thickness direction increases. As a result, heat can be transferred more effectively in the thickness direction of the thermal conductive sheet. In the present invention, the "aspect ratio" can be determined by observing the particulate filler with a SEM (scanning electron microscope), measuring the maximum diameter (long diameter) and the particle diameter (short diameter) in a direction perpendicular to the maximum diameter for any 50 particulate fillers, and calculating the average value of the ratio of the long diameter to the short diameter (long diameter / short diameter).
[0035] <<Particulate filler content>> The content of the particulate filler in the heat conductive sheet is not particularly limited, but is preferably 30% by volume or more, more preferably 35% by volume or more, particularly preferably 40% by volume or more, preferably 55% by volume or less, more preferably 50% by volume or less, even more preferably 45% by volume or less, and particularly preferably 42% by volume or less. If the content of the particulate filler is 30% by volume or more, the thermal conductivity in the thickness direction of the heat conductive sheet is increased, and the heat can be transferred more effectively in the thickness direction of the heat conductive sheet. On the other hand, if the content of the particulate filler is 42% by volume or less, the thickness precision can be further improved while maintaining the flexibility of the heat conductive sheet.
[0036] The content of the particulate filler in the heat conductive sheet is not particularly limited, but is preferably 35% by mass or more, more preferably 40% by mass or more, particularly preferably 45% by mass or more, and preferably 65% by mass or less, more preferably 55% by mass or less, particularly preferably 50% by mass or less. If the content of the particulate filler is 35% by mass or more, the thermal conductivity in the thickness direction of the heat conductive sheet is increased, and the heat can be transferred more effectively in the thickness direction of the heat conductive sheet. On the other hand, if the content of the particulate filler is 65% by mass or less, the thickness precision of the heat conductive sheet can be further improved while maintaining the flexibility of the heat conductive sheet.
[0037] In addition, the content of the particulate filler in the thermal conductive sheet is not particularly limited, but is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, particularly preferably 80 parts by mass or more, and preferably 120 parts by mass or less, more preferably 110 parts by mass or less, and particularly preferably 100 parts by mass or less, per 100 parts by mass of resin. If the content of the particulate filler is 60 parts by mass or more per 100 parts by mass of resin, the thermal conductivity in the thickness direction of the thermal conductive sheet is increased, and the heat can be transferred more effectively in the thickness direction of the thermal conductive sheet. On the other hand, if the content of the particulate filler is 120 parts by mass or less per 100 parts by mass of resin, the thickness precision of the thermal conductive sheet can be further improved while ensuring the flexibility of the thermal conductive sheet.
[0038] <Additives> The heat conductive sheet of the present invention may further contain known additives that can be used to form the heat conductive sheet, if necessary. The additives that can be contained in the heat conductive sheet are not particularly limited, and include, for example, plasticizers such as fatty acid esters such as sebacic acid esters; flame retardants such as red phosphorus flame retardants and phosphate ester flame retardants; toughness improvers such as urethane acrylates; moisture absorbents such as calcium oxide and magnesium oxide; adhesion improvers such as silane coupling agents, titanium coupling agents, and acid anhydrides; wettability improvers such as nonionic surfactants and fluorine surfactants; ion trapping agents such as inorganic ion exchangers; and the like. The additives may be used alone or in combination of two or more.
[0039] If the thermal conductive sheet further contains an additive, the amount of the additive can be, for example, 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the above-mentioned resin, and it is preferable to set it to 10 parts by mass or less.
[0040] <Thermal Conduction Sheet Properties> The thermal conductivity of the thermal conductive sheet in the thickness direction must be 15 W / m·K or more, more preferably 20 W / m·K or more, and even more preferably 25 W / m·K or more. If the thermal conductivity of the thermal conductive sheet in the thickness direction is less than 15 W / m·K, the thermal conductive sheet cannot transfer heat well in the thickness direction. The upper limit of the thermal conductivity of the thermal conductive sheet in the thickness direction is not particularly limited, but is, for example, 45 W / m·K or less. The thermal conductivity of the thermal conductive sheet in the thickness direction can be adjusted by changing the type and content of materials (resin, particulate filler, etc.) used in the manufacture of the thermal conductive sheet, as well as the manufacturing conditions of the thermal conductive sheet. For example, the thermal conductivity of the thermal conductive sheet in the thickness direction can be increased by changing the volume average particle size and / or content of the particulate filler in the thermal conductive sheet. In addition, the thermal conductivity of the thermal conductive sheet in the thickness direction can be increased by manufacturing the thermal conductive sheet using the manufacturing method of the thermal conductive sheet of the present invention described later.
[0041] In addition, the thermal conductive sheet must have a standard deviation of thickness of 3.5 μm or less, preferably 3.0 μm or less, more preferably 2.7 μm or less, and particularly preferably 2.5 μm or less. If the standard deviation of thickness exceeds 3.5 μm, the thickness precision of the thermal conductive sheet is impaired. Therefore, it becomes difficult to make the heat generating body and the heat dissipating body adhere well to each other through the thermal conductive sheet, and the heat transfer from the heat generating body to the heat dissipating body cannot be performed uniformly. The lower limit of the standard deviation of the thickness of the thermal conductive sheet is not particularly limited, but is, for example, 1 μm or more. The standard deviation of the thickness of the thermally conductive sheet can be adjusted by changing the type and content of the materials (resin, particulate filler, etc.) used in the manufacture of the thermally conductive sheet, as well as the manufacturing conditions of the thermally conductive sheet. For example, the standard deviation of the thickness of the thermally conductive sheet can be reduced by manufacturing the thermally conductive sheet using the manufacturing method of the thermally conductive sheet of the present invention described below. More specifically, in the manufacturing method of the thermally conductive sheet of the present invention, the standard deviation of the thickness of the thermally conductive sheet can be reduced by changing the Asker C hardness of the block body, the amount of pressure applied during slicing, the length of the first front surface of the blade used for slicing, etc.
[0042] In addition, the thermal conductive sheet has an average thickness of preferably 70 μm or more, more preferably 80 μm or more, and preferably 250 μm or less, more preferably 200 μm or less, even more preferably 160 μm or less, and particularly preferably 120 μm or less. If the average thickness is 70 μm or more, the strength of the thermal conductive sheet can be ensured, and if it is 250 μm or less, heat can be transferred more effectively in the thickness direction of the thermal conductive sheet.
[0043] The area of the main surface of the thermal conductive sheet is, for example, 30 cm 2 Can be more than 50cm 2 Can be more than 80cm 2 Can be more than 100cm 2 Can be more than 1000cm 2 It can be as follows:
[0044] The surface roughness Sa of both main surfaces of the thermal conductive sheet must be 3.00 μm or less, preferably 2.80 μm or less, more preferably 2.60 μm or less, even more preferably 2.20 μm or less, and particularly preferably 2.00 μm or less. If the surface roughness Sa of both main surfaces exceeds 3.00 μm, the interface resistance becomes high, and when the thermal conductive sheet is used by being sandwiched between a heat generating body and a heat dissipating body, it becomes difficult to make the heat generating body and the heat dissipating body adhere well through the thermal conductive sheet, and the heat transfer from the heat generating body to the heat dissipating body cannot be performed uniformly. The lower limit of the surface roughness Sa of the main surface of the thermal conductive sheet is not particularly limited, but is, for example, 1.0 μm or more. The surface roughness Sa of the main surface of the thermal conductive sheet can be adjusted by changing the type and content of the materials (resin, particulate filler, etc.) used in the manufacture of the thermal conductive sheet, as well as the manufacturing conditions of the thermal conductive sheet. For example, the surface roughness Sa of the thermal conductive sheet can be reduced by manufacturing the thermal conductive sheet using the manufacturing method of the thermal conductive sheet of the present invention described below. More specifically, in the manufacturing method of the thermal conductive sheet of the present invention, the surface roughness Sa of the main surface of the thermal conductive sheet can be reduced by changing the length of the first front surface of the blade used for slicing, the surface roughness of the first front surface of the blade used for slicing, the length of the second front surface of the blade used for slicing, the surface roughness of the second front surface of the blade used for slicing, and the like.
[0045] In addition, the absolute value of the difference between the surface roughness Sa of one main surface and the surface roughness Sa of the other main surface of the thermal conductive sheet is preferably 0.40 μm or less, more preferably 0.30 μm or less, even more preferably 0.20 μm or less, and particularly preferably 0.10 μm or less. If the absolute value of the difference between the surface roughness Sa of one main surface and the surface roughness Sa of the other main surface is 0.40 μm or less, the handleability, such as the ease of gripping with a robot arm, can be improved. The lower limit of the absolute value of the difference between the surface roughness Sa of one main surface and the surface roughness Sa of the other main surface is not particularly limited, but is, for example, 0.01 μm or more.
[0046] (Method of manufacturing thermal conductive sheet) The thermally conductive sheet of the present invention described above can be manufactured, for example, by using the manufacturing method of the thermally conductive sheet of the present invention. Here, the manufacturing method of the thermally conductive sheet of the present invention includes at least a step (slicing step) of slidably supporting a block body containing a resin and a particulate filler by a slide surface, and, in a state in which a blade with a tip end protruding from the slide surface is supported, sliding the block body while pressing it against the slide surface, thereby slicing the block body with the blade. Furthermore, according to the method for producing a thermally conductive sheet of the present invention, it is possible to obtain a thermally conductive sheet which has both smooth main surfaces, has sufficient thickness accuracy, and is capable of transferring heat well in the thickness direction.
[0047] <Slicing process> In the slicing step, as described above, the block body is slidably supported by the sliding surface while a blade with a tip protruding from the sliding surface is supported. The block body is slid against the sliding surface while being pressed against the sliding surface. The block body is sliced with the blade, the length of which is 0.8 mm or more and the surface roughness Sa of which is 1.00 μm or less, to cut out a thermally conductive sheet from the block body.
[0048] <<Block letters>> The block body includes a resin and a particulate filler, and may further include an optional additive. The block body preferably has an Asker C hardness of 90 or less. The block body preferably has a dynamic friction coefficient of 2.5 or less.
[0049] [Resins, particulate fillers, and additives] The suitable types, properties and content ratios of the resin and particulate filler contained in the block body, as well as the optional additives contained therein, may be the same as the suitable types, properties and content ratios described above for the thermal conductive sheet of the present invention.
[0050] [Asker C hardness] Here, the block body has an Asker C hardness of preferably 90 or less, more preferably 85 or less, particularly preferably 80 or less, preferably 30 or more, more preferably 40 or more, even more preferably 50 or more, and particularly preferably 60 or more. If the Asker C hardness is 90 or less, the blade can easily penetrate the block body, so that the thickness precision of the thermally conductive sheet obtained by slicing the block body can be more sufficiently ensured. On the other hand, if the Asker C hardness is 30 or more, the vibration of the blade tip caused by the adhesion of the block body during slicing can be suppressed, and thus a thermally conductive sheet with even more excellent thickness precision can be obtained. The Asker C hardness of the block body can be adjusted by changing the type and content of materials (resin, particulate filler, etc.) used in manufacturing the block body, or the manufacturing method of the block body. In the present invention, the "Asker C hardness" is a value measured at a temperature of 23°C using a hardness meter in accordance with the Asker C method of the Society of Rubber Industry, Japan (SRIS), and can be measured, for example, using the method described in the examples of this specification.
[0051] [Kinematic friction coefficient] Here, the coefficient of dynamic friction of the block body is preferably 0.5 or less, more preferably 0.3 or less, and preferably 0.05 or more, and more preferably 0.1 or more. If the coefficient of dynamic friction is 0.5 or less, the friction generated between the block body and the blade can be reduced, enabling smooth slicing. Generally, the coefficient of friction is 0.01 or more. The dynamic friction coefficient of the block body can be adjusted by changing the type and content of materials (resin, particulate filler, etc.) used in manufacturing the block body, or by changing the manufacturing method of the block body. In the present invention, the "dynamic friction coefficient" can be measured in accordance with ASTM D1894 using, for example, a surface property measuring instrument TYPE: 14FW (manufactured by Shinto Scientific Co., Ltd.).
[0052] <<Blade>> The shape of the blade used to slice the above-mentioned block body may be a "double-edged" blade with cutting edges on both sides of the blade tip, or a "single-edged" blade with a cutting edge only on the front side (front surface) of the blade; however, a "single-edged" blade is preferred from the viewpoint of ensuring sufficient thickness accuracy of the obtained thermal conductive sheet. The shape of the blade may be an "asymmetric blade" having a cross section that is asymmetric with respect to the central axis passing through the very tip of the blade tip, or a "symmetric blade" having a symmetric cross section. The number of blades constituting the blade is not particularly limited, and may be, for example, a "single blade" consisting of one blade, or a "two blades" consisting of two blades. FIG. 1 shows an example of slicing a block body (laminated body) using a plane. As shown in FIG. 1, when the blade is composed of one blade, it is composed of one blade 10. When the blade is composed of two blades, it is composed of a front blade and a back blade. The heights of the tips of the front blade and the back blade protruding from the slit portion may be the same or different. That is, the tips of the front blade and the back blade may be aligned or may be shifted vertically. The material of the blade used to slice the above-mentioned block body is not particularly limited, but from the viewpoint of ensuring sufficient smoothness on both main surfaces, it is preferable that the blade be made of a metal such as ceramic, cemented carbide, high-speed tool steel (high-speed steel), steel, etc., and cemented carbide is more preferable in terms of the balance of hardness of the blade itself and the ease of processing the blade.
[0053] The blade used to slice the block body described above, as shown in FIG. 1, for example, has a first front surface 10a that contacts the block body 20, a back surface 10c that intersects with the first front surface 10a, a cutting edge 10d formed at the intersection corner between the first front surface 10a and the back surface 10c, and a second front surface 10b that extends from an edge 10e of the first front surface 10a opposite to the cutting edge 10d side and is located closer to the back surface 10c than the first front surface 10a. That is, the blade used to slice the block body has a first surface and a second surface. The first surface is formed on the cutting edge side and is the surface that comes into contact with the block body to be sliced during slicing, while the second surface is at a predetermined angle to the first surface and is provided to reduce the area of contact with the block body to be sliced.
[0054] Furthermore, as mentioned above, the length of the first front surface of the blade must be 0.8 mm or more, preferably 1.0 mm or more, and more preferably 3.0 mm or more, and is preferably 10.0 mm or less, and more preferably 5.0 mm or less. If the length of the first front surface of the blade is less than 0.8 mm, the thickness precision of the thermally conductive sheet obtained by slicing the block body is compromised, whereas if the length of the first front surface is 10.0 mm or less, the smoothness of the surface of the thermally conductive sheet obtained by slicing the block body can be ensured. Furthermore, the surface roughness Sa of the first front surface of the blade must be 1.00 μm or less as described above, preferably 0.80 μm or less, more preferably 0.40 μm or more, and even more preferably 0.50 μm or more. If the surface roughness Sa of the first front surface of the blade exceeds 1.00 μm, the smoothness of side B of the thermal conductive sheet obtained by slicing the block body is impaired due to friction between the block body and the front surface. The lower limit of the surface roughness Sa of the first front surface of the blade is not particularly limited, but is, for example, 0.30 μm or more.
[0055] Furthermore, as described above, the length of the second front surface of the blade is preferably 20.0 mm or more, more preferably 23.0 mm or more, and particularly preferably 25.0 mm or more, and is preferably 50.0 mm or less, more preferably 40.0 mm or less, and even more preferably 30.0 mm or less. When the length of the second front surface of the blade is 20.0 mm or more, the strength of the thermally conductive sheet obtained by slicing the block body can be ensured, whereas when the length of the second front surface is 50.0 mm or less, the smoothness of the surface of the thermally conductive sheet obtained by slicing the block body can be ensured. Furthermore, the surface roughness Sa of the second front surface of the blade is preferably 1.00 μm or less, as described above, more preferably 0.80 μm or less, and particularly preferably 0.50 μm or more. If the surface roughness Sa of the second front surface of the blade is 1.00 μm or less, the smoothness of the surface of the thermally conductive sheet obtained by slicing the block can be more reliably ensured. The lower limit of the surface roughness Sa of the second front surface of the blade is not particularly limited, but is, for example, 0.50 μm or more.
[0056] The first blade angle (the angle between the first front surface and the back surface) of the blade is not particularly limited and can be, for example, 10° to 45°. For example, as shown in FIG. 1, the blade angle θ1 can be set within the above range. Furthermore, the second blade angle (the angle between the second front surface and the back surface) of the blade is not particularly limited and can be, for example, 10° to 30°. For example, as shown in FIG. 1, the blade angle θ2 can be set within the above range.
[0057] <<Slice>> [Slice Speed] The speed at which the block body (laminated body) is sliced (in other words, the relative speed at which the block body and the blade are brought into contact) must be 5 m / min or more. The speed at which the block body (laminated body) is sliced is not particularly limited, but is preferably 12 m / min or more, more preferably 30 m / min or more, and is preferably, for example, 120 m / min or less. If the speed at which the block body (laminated body) is sliced is 12 m / min or more, productivity can be improved and the deterioration of surface roughness caused by the blade compressing the block body as it advances can be suppressed. Also, if the speed at which the block body (laminated body) is sliced is 120 m / min or less, the impact of the collision between the block body and the blade can be suppressed from becoming large, and the block body (especially the blade entry portion) can be sliced more uniformly.
[0058] The slicing speed may be controlled by changing the speed at which the block body 20 advances (cuts) into the fixed blade 10 as shown in Fig. 1; by changing the speed at which the blade advances (cuts) into the fixed block body; or by changing the relative speed at which the blade and the block body advance (cut) into each other. From the viewpoint of workability, it is preferable to control the slicing speed by mechanical control.
[0059] [Slice Direction] In the above slicing, it is preferable to slice the block body in a plane parallel to the lamination direction (in other words, so that the main surface of the heat conductive sheet obtained by slicing has a lamination cross section). For example, as shown in Fig. 1, if the block body 20 is sliced in a plane parallel to the lamination direction A of the primary sheet 20a, the heat conductive sheet obtained by slicing can exhibit desired characteristics in the thickness direction. In the present invention, the term "surface parallel to the stacking direction" also includes a surface having an inclination of about 30° or less with respect to a direction parallel to the stacking direction.
[0060] Here, as an example, a case where slicing is performed using a plane shown in FIG. 1 will be described. First, the stacking side 20b of the block body 20 is supported by the sliding surface 30a so that the block body 20 can slide in a direction in which the stacking side 20b and the sliding surface 30a of the planer are parallel. That is, according to FIG. 1, the stacking direction A is also horizontal with respect to the horizontally installed planer, the stacking side 20c faces upward and the stacking side 20b faces downward, and the stacked body 1 is placed on the sliding surface 30a so that the top surface 20d faces the blade 10. In addition, the tip of the blade 10 for slicing protrudes to an arbitrary degree from the sliding surface 30a. In the example of FIG. 1, the tip of the blade 10 having a blade angle θ1 protrudes from the sliding surface 30a at an angle α. 1, the block body 20 supported on the slide surface 30a is slid in a direction parallel to the slide surface 30a (slide direction) at a predetermined slicing speed (slide speed) while being pressed from the stacking side surface 20c side to the slide surface 30a side with an arbitrary pressure. Note that the sliding speed at this time is the above-mentioned predetermined slicing speed. By sliding the block body 20 in this manner, the top surface 20d enters the blade 10 at a predetermined sliding speed, and the block body 20 is sliced in a plane parallel to the lamination direction A.
[0061] The pressure applied when pressing the block body against the slide surface is preferably 0.05 MPa or more, more preferably 0.10 MPa or more, and particularly preferably 0.20 MPa or more, and is preferably 0.50 MPa or less, more preferably 0.40 MPa or less, and particularly preferably 0.30 MPa or less. When the pressure is 0.05 MPa or more, the thickness precision of the thermally conductive sheet obtained by slicing the block body can be ensured, while when the pressure is 0.50 MPa or less, crushing of the block body can be suppressed. When the block body is a laminate obtained by stacking primary sheets in a lamination step described below, it is preferable to slice the block body, which is a laminate, while applying pressure in a direction perpendicular to the stacking direction, in order to easily slice the block body and ensure sufficient thickness precision of the obtained thermal conductive sheet.
[0062] From the viewpoint of easily slicing the block body and ensuring sufficient thickness precision of the resulting thermally conductive sheet, the temperature of the block body during slicing is preferably −20° C. or higher and 80° C. or lower, and more preferably −10° C. or higher and 50° C. or lower.
[0063] [Slice Angle] Here, the slice angle β (sometimes called the "entrance angle" or "penetration angle") formed between the stacking direction of the block bodies and the extending direction of the blade can be set within a range of 0° to 90°. 2(a), the stacking side surface 20f contacts the blade 10 so that the stacking direction A of the primary sheets in the block body 20 (laminate) and the extension direction E of the blade 10 are parallel (slicing angle β=0°). In FIGS. 2(b) to 2(d), the stacking direction A of the primary sheets in the block body 20 (laminate) and the extension direction E of the blade 10 form an angle, and the top surface 20d and the stacking side surface 20f contact so as to enter the blade 10 (slicing angles β=15°, 45°, and 75°). And in FIG. 2(e), the top surface 20d contacts the blade 10 so that the stacking direction A of the primary sheets in the block body 20 (laminate) and the extension direction E of the blade 10 form a right angle (slicing angle β=90°). From the viewpoint of reducing the impact at the time of the initial collision and improving the thickness surface accuracy, the slice angle β is preferably more than 0°, more preferably 1° or more, even more preferably 5° or more, even more preferably 30° or more, and particularly preferably 40° or more. Similarly, from the above viewpoint, the slice angle β is preferably less than 90° within the range of 0° to 90°, more preferably 89° or less, even more preferably 85° or less, even more preferably 60° or less, and particularly preferably 50° or less. And, it is even more preferable that the slice angle β is 45°.
[0064] The slicing angle may be controlled by changing the angle at which the block body enters (cuts) relative to a fixed blade, or by changing the angle at which the blade enters (cuts) relative to a fixed block body, or by changing the relative angle at which the blade and block body enter (cut) closer to each other.
[0065] As described above, the method for slicing the block body is not particularly limited as long as, for example, as shown in FIG. 1, the block body 20 is slidably supported by the sliding surface 30a, and the block body 20 is slid against the sliding surface 30a while the blade 10, whose tip portion protrudes from the sliding surface 30a, is supported. As described above, the block body 20 is sliced by, for example, sliding in the stacking direction A of the primary sheet 20a while being pressed against the slide surface 20a, and a thermally conductive sheet (not shown) is newly generated on the rear surface 10c side of the blade 10. Here, the main surface of the newly generated thermally conductive sheet on the upper side in Fig. 1 is referred to as surface A, and the main surface on the lower side in Fig. 1 is referred to as surface B. According to the present invention, at least the length and surface roughness Sa of the first front surface 10a of the blade 10 are adjusted within a predetermined range, and preferably the surface roughness Sa of the second front surface 10b of the blade 10 is adjusted, so that damage received when the block body 20 is slid in the stacking direction A of the primary sheet 20a while being pressed against the sliding surface 20a (damage received by the lower surface of the block body 20 in FIG. 1 (side B of the thermal conduction sheet to be generated next) from the second front surface 10b of the blade 10 at the step 30b or groove 40) can be reduced. From the viewpoint of preventing the smoothness of the lower surface of the block body 20 in FIG. 1 (side B of the thermal conductive sheet to be generated next) from being impaired, it is preferable to move the block body 20 without abutting against the sliding surface 30 a when returning the block body 20 from the position after sliding to the position before sliding (the position of the block body 20 in FIG. 1).
[0066] <Other processes> Other steps that may be optionally included in the method for producing a thermally conductive sheet of the present invention are not particularly limited. For example, in the manufacturing method of the thermal conductive sheet of the present invention, before the above-mentioned slicing step, a step (stacking step) can be carried out in which multiple primary sheets containing resin and particulate filler are stacked in the thickness direction, or the primary sheets are folded or rolled to obtain a block body. In the method for producing a thermally conductive sheet of the present invention, a step of heating the block body (heating step) can be carried out prior to the above-mentioned slicing step. In the method for producing a thermally conductive sheet of the present invention, a step of pressing the thermally conductive sheet obtained after the slicing step in the thickness direction (pressing step) may be carried out as long as the effect of the present invention is not significantly impaired. However, from the viewpoint of suppressing a decrease in the thermal conductivity of the obtained thermally conductive sheet in the thickness direction, it is preferable that the method for producing a thermally conductive sheet of the present invention does not include a pressing step. The lamination step and the heating step as other steps will be described in detail below.
[0067] <<Lamination process>> As described above, in the lamination step, a plurality of primary sheets are laminated in the thickness direction, or the primary sheets are folded or rolled to obtain a block body, which is a laminate.
[0068] [1st sheet] The primary sheet comprises a resin and a particulate filler, and may optionally further comprise additives.
[0069] -Resin, particulate fillers, and additives- The suitable types, properties and content ratios of the resin and particulate filler contained in the primary sheet, as well as the optional additives contained therein, may be the same as those described above for the block body and the thermally conductive sheet of the present invention.
[0070] -Characteristics of the first sheet- The tensile strength of the primary sheet is preferably 0.3 MPa or more, more preferably 1.0 MPa or more, even more preferably 1.5 MPa or more, and preferably 3.0 MPa or less, more preferably 2.5 MPa or less, and even more preferably 2.0 MPa or less. If the tensile strength is 0.3 MPa or more, the Asker C hardness of the block body obtained by stacking the primary sheets is increased. Therefore, it is possible to obtain a heat conductive sheet with even better thickness accuracy by suppressing the vibration of the blade tip when slicing the block body. On the other hand, if the tensile strength is 3.0 MPa or less, the Asker C hardness of the block body obtained by stacking the primary sheets is not excessively increased. Therefore, the block body can be easily sliced, and the thickness accuracy of the obtained heat conductive sheet (particularly, the thickness accuracy when the slice width is reduced to reduce the thickness of the heat conductive sheet) can be sufficiently ensured. The tensile strength of the primary sheet can be adjusted by changing the type and content of materials (resin, particulate filler, etc.) used in the production of the primary sheet, or the production method of the primary sheet. For example, the tensile strength of the primary sheet can be increased by increasing the content of resin in the primary sheet.
[0071] Furthermore, the thickness (average thickness) of the primary sheet is not particularly limited, and can be, for example, 0.05 mm or more and 2 mm or less. The "thickness (average thickness)" of the primary sheet can be measured in the same manner as the "average thickness" of the thermally conductive sheet.
[0072] - How to prepare the primary sheet - The method for preparing the primary sheet is not particularly limited.The primary sheet can be obtained, for example, by molding a composition containing resin, particulate filler, and any additives by a known molding method such as press molding, rolling molding, or extrusion molding.
[0073] [Formation of blocks by lamination, etc.] The formation of a block body by stacking the primary sheets is not particularly limited, and may be performed using a stacking device or manually. The formation of a block body by folding a thermally conductive sheet is not particularly limited, and may be performed by folding the primary sheet at a fixed width using a folding machine. The formation of a block body by winding the primary sheet is not particularly limited, and may be performed by winding the primary sheet around an axis parallel to the short side or long side of the primary sheet.
[0074] <<Heating process>> Here, for example, the block body obtained through the lamination step described above may be subjected to the slicing step as it is, or may be subjected to the slicing step after being further heated. The heating temperature in the heating step may be, for example, 50° C. or higher and 170° C. or lower, and the heating time may be, for example, 1 minute or higher and 8 hours or lower. By passing through the heating step, it is possible to adjust the adhesion of the block body in the lamination direction. For example, when the block body contains a thermoplastic resin, it is possible to increase the adhesion of the block body in the lamination direction by carrying out the heating step. EXAMPLES
[0075] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%" and "parts" expressing amounts are by mass unless otherwise specified. In the examples and comparative examples, the particle size distribution and volume average particle diameter, the content (volume fraction) of particulate filler, the surface roughness Sa of the first and second front surfaces of the blade, the Asker C hardness of the block body, and the average thickness, standard deviation of the thickness, surface roughness Sa, and thermal conductivity in the thickness direction of the thermal conductive sheet were each measured or evaluated according to the following methods.
[0076] <Volume average particle size> 1 g of the thermal conductive sheet was placed in methyl ethyl ketone as a solvent, and the resin components of the thermal conductive sheet were dissolved to obtain a suspension in which the particulate filler (expanded graphite) contained in the thermal conductive sheet was separated and dispersed. Next, the particle diameter of the particulate filler contained in the suspension was measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model "LA960"). Then, a particle size distribution curve was created with the obtained particle diameter on the horizontal axis and the volumetric frequency of particles on the vertical axis. Then, the particle diameter (D50) at which the cumulative volume calculated from the small diameter side was 50% was obtained in the particle size distribution curve, and this was taken as the volume average particle diameter value of the particulate filler. <Particulate filler content (volume fraction)> The content ratio (volume fraction) of the particulate filler in the primary sheet was calculated by dividing the weight of each material used in forming the primary sheet by the specific gravity of that material, which was taken as the volume of that material. The calculation was performed assuming that the specific gravity of the resin was 1.77 for both liquid resin and solid resin, the specific gravity of the particulate filler (expanded graphite) was 2.25, and the specific gravity of the additive was 1.17. <Surface roughness Sa of the first and second front surfaces of the blade> The surface roughness Sa of the first and second front surfaces of the blade was measured using a three-dimensional shape measuring instrument (manufactured by Keyence Corporation, product name "One Shot 3D Measurement Macroscope") at a magnification of 40 times, and the observation range was 5.7 mm × 7.6 mm. <Asker C hardness of block body (laminated body)> The Asker C hardness of the block body (laminate) was measured at 25°C using a hardness tester (manufactured by Kobunshi Keiki Co., Ltd., product name "ASKER CL-150LJ") in accordance with the Asker C method of the Society of Rubber Industry Standards of Japan (SRIS). Specifically, the obtained block body (laminate) was left to stand in a constant temperature room maintained at a temperature of 25°C for 48 hours or more to prepare a test specimen. Next, the hardness tester was placed so that the needle tip was 2 cm away from the laminate surface, and a damper was lowered to cause the block body (laminate) and the damper to collide. The Asker C hardness of the block body (laminate) 60 seconds after the collision was measured twice using a hardness tester (manufactured by Kobunshi Keiki Co., Ltd., product name "ASKER CL-150LJ"), and the average of the measurement results was used. <Average thickness> Using a film thickness gauge (manufactured by Mitutoyo, product name "Digimatic Indicator ID-C112XBS"), the thickness was measured at five points, approximately the center and each of the four corners of the thermal conductive sheet, and the average thickness (μm) was calculated. <Standard deviation of thickness> A film thickness gauge (manufactured by Mitutoyo, product name "Digimatic Indicator ID-C112XBS") was used to measure the thickness at five points, approximately the center and each of the four corners (squares), of the thermal conductive sheet, and the standard deviation (μm) of the measured thicknesses was calculated. <Surface roughness Sa of thermal conductive sheet> The surface roughness Sa of the thermal conductive sheet was measured using a three-dimensional shape measuring instrument (manufactured by Keyence Corporation, product name "One Shot 3D Measurement Macroscope"). Here, the thermal conductive sheet cut into an arbitrary size of approximately 1 cm or more was used as a sample, the analysis range was 1 cm x 1 cm, and the three-dimensional shape was measured for each of the front and back sides of the sample. The measurement results of the three-dimensional shape were further filtered (2.5 mm) by software to remove the waviness components, and the surface roughness Sa (μm) was automatically calculated. The surface roughness Sa was measured for each of side A (a surface newly generated by inserting a new blade) and side B (a surface already generated by inserting the previous blade). <Thermal conductivity in the thickness direction> For the thermal conductive sheet, the thermal diffusivity α (m 2 / s), specific heat at constant pressure Cp (J / g K), and specific gravity ρ (g / m 3 ) were measured by the following methods. [Thermal diffusivity in the thickness direction α] The thermal diffusivity of the thermal conductive sheet was measured using a thermal diffusivity / thermal conductivity measuring device (ai-Phase Mobile 1u, manufactured by Ai-Phase Corporation) in accordance with the provisions of ISO22007-3. [Specific heat at constant pressure Cp] The specific heat was measured at 25° C. under a temperature increase rate of 10° C. / min using a differential scanning calorimeter (manufactured by Rigaku, product name "DSC8230"). [Specific gravity ρ (density)] The measurement was performed using an automatic specific gravity meter (manufactured by Toyo Seiki Co., Ltd., product name "DENSIMETER-H"). Then, each measured value is calculated using the following formula (I): λ = α × Cp × ρ (I) The thermal conductivity λ (W / m K) in the thickness direction of the thermal conductive sheet at 25°C was calculated by substituting <Thermal resistance value> The thermal resistance value of the thermal conductive sheet was measured using a thermal resistance tester (manufactured by Hitachi Technology & Services Co., Ltd., product name "Resin Material Thermal Resistance Measuring Device"). Here, the thermal conductive sheet cut into an approximately 1 cm square was used as a sample, and the thermal resistance value (°C / W) was measured when a pressure of 0.1 MPa and 0.9 MPa was applied at a sample temperature of 50°C. The smaller the thermal resistance value, the better the thermal conductivity of the thermal conductive sheet, and for example, indicates that the heat dissipation characteristics are excellent when interposed between a heat generating body and a heat sink.
[0077] Example 1 <Formation of the primary sheet> 70 parts of thermoplastic fluororesin (manufactured by Daikin Industries, Ltd., product name "Daiel G-101") that is liquid at room temperature and normal pressure as a resin, 30 parts of thermoplastic fluororesin (manufactured by 3M Japan, Ltd., product name "Dyneon FC2211") that is solid at room temperature and normal pressure as a resin, and 90 parts of expanded graphite (manufactured by Ito Graphite Industries, Ltd., product name "EC300", volume average particle size: 50 μm) as a particulate filler were stirred and mixed at a temperature of 150 ° C. for 20 minutes using a pressure kneader (manufactured by Nippon Spindle). Next, the resulting mixture was put into a crusher (manufactured by Osaka Chemical Co., Ltd., product name "Wonder Crush Mill D3V-10") and crushed for 10 seconds. 50 g of the crushed mixture was sandwiched between a 50 μm-thick sandblasted polyethylene terephthalate (PET) film (protective film) and roll-formed under the conditions of a roll gap of 550 μm, a roll temperature of 50°C, a roll linear pressure of 50 kg / cm, and a roll speed of 1 m / min to obtain a primary sheet with a thickness of 0.8 mm. <Lamination process> The obtained primary sheet was cut into a size of 150 mm length x 150 mm width x 0.8 mm thickness, 100 sheets were stacked in the thickness direction of the primary sheet, and pressed in the stacking direction at a temperature of 120°C and a pressure of 0.1 MPa for 3 minutes to obtain a block (laminate) with a height of about 80 mm. The Asker C hardness of the obtained block was then measured. The results are shown in Table 1. <Slicing process> Thereafter, while pressing the side (surface along the lamination direction) of the block body (laminate) against the slide surface with a pressure of 0.3 MPa, the block body (laminate) was sliced in the lamination direction (in other words, in the direction that coincides with the normal line of the main surface of the laminated primary sheets) using a woodworking slicer (Marunaka Iron Works Co., Ltd., product name "Super Finishing Planer Super Mecha S") to obtain a thermally conductive sheet of length 150 mm x width 150 mm x thickness 0.10 mm. The slicing was performed by sliding the block body (laminate) on the slide surface at a sliding speed of 1000 mm / sec. A single blade A having the following properties was used as the slicing blade of the woodworking slicer. The temperature of the block body was room temperature. <<Characteristics of Single-Edged A>> Blade angle A (see FIG. 1: angle θ1 between first front surface 10a and back surface 10c): 40° Blade angle B (see FIG. 1: angle θ2 between second front surface 10b and back surface 10c): 20° Maximum blade thickness: 9mm Material: Carbide (tungsten carbide) Rockwell hardness: 90 Silicone coating on the blade surface: None Tip curvature radius R: 10 μm Length of first front surface: 1.0mm Surface roughness of the first front surface Sa: 0.43 μm Length of second front surface: 25.0mm Surface roughness of the second front surface Sa: 0.61 μm The average thickness, standard deviation of the thickness, surface roughness Sa, and thermal conductivity in the thickness direction of the obtained thermal conductive sheet were measured. The results are shown in Table 1.
[0078] Example 2 A primary sheet, a block body, and a heat conductive sheet were produced and various evaluations were performed in the same manner as in Example 1, except that a single edge B having the following properties was used instead of the single edge A in Example 1. The results are shown in Table 1. <<Characteristics of Single-edged B>> Blade angle A (see FIG. 1: angle θ1 between first front surface 10a and back surface 10c): 40° Blade angle B (see FIG. 1: angle θ2 between second front surface 10b and back surface 10c): 20° Maximum blade thickness: 9mm Material: Carbide (tungsten carbide) Rockwell hardness: 90 Silicone coating on the blade surface: None Tip curvature radius R: 10 μm Length of first front surface: 3.0mm Surface roughness of the first front surface Sa: 0.43 μm Length of second front surface: 23.0mm Surface roughness of the second front surface Sa: 0.61 μm
[0079] Example 3 A primary sheet, a block body, and a heat conductive sheet were produced and various evaluations were performed in the same manner as in Example 1, except that a single blade C having the following properties was used instead of the single blade A in Example 1. The results are shown in Table 1. <<Characteristics of Single-edged C>> Blade angle A (see FIG. 1: angle θ1 between first front surface 10a and back surface 10c): 40° Blade angle B (see FIG. 1: angle θ2 between second front surface 10b and back surface 10c): 20° Maximum blade thickness: 9mm Material: High speed tool steel (HSS) Rockwell hardness: 82 Silicone coating on the blade surface: None Tip curvature radius R: 10 μm Length of first front surface: 1.0mm Surface roughness of the first front surface Sa: 0.75μm Length of second front surface: 25.0mm Surface roughness of the second front surface Sa: 0.86 μm
[0080] Comparative Example 1 A primary sheet, a block body, and a heat conductive sheet were produced and various evaluations were performed in the same manner as in Example 1, except that a single edge D having the following properties was used instead of the single edge A in Example 1. The results are shown in Table 1. <<Characteristics of Single-edged D>> Blade angle A (see FIG. 1: angle θ1 between first front surface 10a and back surface 10c): 40° Blade angle B (see FIG. 1: angle θ2 between second front surface 10b and back surface 10c): 20° Maximum blade thickness: 9mm Material: High speed tool steel (HSS) Rockwell hardness: 82 Silicone coating on the blade surface: None Tip curvature radius R: 10 μm Length of first front surface: 1.0mm Surface roughness of the first front surface Sa: 1.25 μm Length of second front surface: 25.0mm Surface roughness of the second front surface Sa: 0.94 μm
[0081] Comparative Example 2 In Example 1, instead of slicing the block body (laminate) in the stacking direction using a wood slicer while pressing the side of the block body (laminate) against the slide surface with a pressure of 0.3 MPa, the block body (laminate) was sliced in the stacking direction using a wood slicer without pressing the side of the block body (laminate) against the slide surface with a pressure of 0.3 MPa (i.e., only by the weight of the block body (laminate)), a primary sheet, a block body, and a heat conductive sheet were produced in the same manner as in Example 1, and various evaluations were performed. The results are shown in Table 1.
[0082] Comparative Example 3 In Example 3, in forming the primary sheet, 50 parts of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC300", volume average particle size: 50 μm) were used as the particulate filler instead of 90 parts of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC100", volume average particle size: 200 μm) were used as the particulate filler instead of 90 parts of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC300", volume average particle size: 50 μm). A primary sheet, a block body, and a heat conductive sheet were produced and various evaluations were performed in the same manner as in Example 3. The results are shown in Table 1.
[0083] Comparative Example 4 In Example 1, when forming the primary sheet, 70 parts of a thermoplastic fluororesin that is liquid at room temperature and normal pressure (manufactured by Daikin Industries, Ltd., product name "Daiel G-101") as a resin, 30 parts of a thermoplastic fluororesin that is solid at room temperature and normal pressure (manufactured by 3M Japan Ltd., product name "Dainion FC2211") as a resin, and 90 parts of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC300", volume average particle diameter: 50 μm) as a particulate filler were used to obtain a thermal conductive sheet of length 150 mm x width 150 mm x thickness 0.10 mm. Instead of using 45 parts of a thermoplastic fluororesin that is liquid at room temperature and normal pressure (manufactured by Daikin Industries, Ltd., product name "Dainion FC2211") as a resin and 40 parts of a thermoplastic fluororesin that is solid at room temperature and normal pressure (manufactured by 3M Japan Ltd., product name "Dainion FC2211") as a resin, A primary sheet, a block, and a thermally conductive sheet were produced in the same manner as in Example 1, except that a secondary sheet (a slice of the block) having a length of 150 mm, a width of 150 mm, and a thickness of 0.50 mm (500 μm) was obtained using 85 parts of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC100", volume average particle diameter: 200 μm) as a particulate filler, and 5 parts by mass of sebacic acid ester (manufactured by Daihachi Chemical Industry Co., Ltd., product name "DOS") as a plasticizer. The secondary sheet was then pressed (post-treatment process) by heating the press plate to 50°C using a precision hot press machine (manufactured by Shinto Kogyo Co., Ltd., product name "CYPT-20") and pressing the secondary sheet at a pressure of 2.6 MPa for 30 seconds to obtain a thermally conductive sheet having a length of 150 mm, a width of 150 mm, and a thickness of 0.125 mm (125 μm). Various evaluations were performed. The results are shown in Table 1.
[0084] [Table 1]
[0085] From Table 1, it can be seen that the thermally conductive sheets of Examples 1 to 3 have both smooth main surfaces. It can also be seen that the thermal conductivity in the thickness direction of the thermally conductive sheets of Examples 1 to 3 is small, and heat can be transferred well in the thickness direction. Furthermore, it can be seen that the thermally conductive sheets of Examples 1 to 3 have excellent thickness precision, since the standard deviation of the thickness is small. [Industrial Applicability]
[0086] According to the present invention, it is possible to provide a thermally conductive sheet having both smooth main surfaces, sufficient thickness accuracy, and capable of excellent heat transfer in the thickness direction, as well as a method for manufacturing the thermally conductive sheet. [Explanation of symbols]
[0087] 10 Blades 10a 1st front 10b 2nd front 10c back side 10d cutting edge 10e edge 20 Block Letters 20a Primary Sheet 20b Laminated side 20c laminated side 20d Top 20e Bottom 20f laminated side 30 units 30a Slide surface 30b Step 40 grooves A: Stacking direction of primary sheet 20a E Blade extension direction θ1: Angle between the first front surface 10a and the back surface 10c (blade angle A) θ2: Angle between the second front surface 10b and the back surface 10c (blade angle B) α angle β Slice Angle
Claims
1. Contains a resin and a particulate filler, The thermal conductivity in the thickness direction is 25 W / m K or more, The standard deviation of the thickness is 3.5 μm or less, The surface roughness Sa of both main surfaces is 3.00 μm or less, The resin includes both liquid and solid resins, The content of the liquid resin in the resin is 70% by mass or more and 95% by mass or less, A thermally conductive sheet having a content of the particulate filler of 40 volume % or more and 55 volume % or less.
2. The thermal conductive sheet according to claim 1 , having an average thickness of 250 μm or less.
3. The thermal conductive sheet according to claim 1 or 2, wherein the particulate filler has a volume average particle diameter of 30 μm or more and 150 μm or less.
4. 4. The thermal conductive sheet according to claim 1, wherein an absolute value of a difference between a surface roughness Sa of one principal surface and a surface roughness Sa of the other principal surface is 0.40 μm or less.
Citation Information
Patent Citations
Installing method of split threeephase transformer
JP1981021306A
Methods of manufacturing composite material sheet and thermally conductive sheet
JP2017141345A
Thermally conductive sheet and method for producing the same
JP2018067695A
Slicing method of laminate and manufacturing method of composite sheet
JP2018089733A
Heat-conductive sheet
JP2019024045A